Pengaruh Fasilitas Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PDAM Tirta Bhagasasi Cabang Cikarang Barat - Dera Herliana; Cahyadi Husadha; Tutiek Yoganingsih (Jurnal Riset dan Inovasi Manajemen, 2024)
This research aims to find out whether employee performance can influence the relationship between work facilities and work discipline that researchers found at PDAM Tirta Bhagasasi West Cikarang Branch. By using quantitative research methods, the population and sample were generated from employees of PDAM Tirta Bhagasasi West Cikarang Branch using the saturated sample method. The sample used in this research consisted of 33 employees as respondents according to the number of employees at PDAM Tirta Bhagasasi West Cikarang Branch. This research reveals that the work facility variable has a positive effect on employee performance. However, the work discipline variable has a negative effect on employee performance.